Pembelajaran Musik Kolaboratif Orff dan Jigsaw untuk Menstimulasi Kemampuan Kerja Sama Siswa Kelas V SD - Nadia Ananta Ramadaniah; Resa Respati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Collaborative skills are one of the essential 21st-century skills that should be developed starting in elementary school. This study aims to describe the collaborative skills of fifth-grade elementary school students following the implementation of the Orff Method based on the Jigsaw Model. The approach used was a descriptive quantitative study with a one-shot case study design. The research subjects were all 37 fifth-grade students at SDN 1 Saguling, Baregbeg Subdistrict, Ciamis Regency. Data were collected using a collaboration skills observation sheet consisting of 15 indicators based on five aspects of Johnson & Johnson’s (2014) theory, with a rating scale of 1–4. The results of the study indicate that the overall average final score for students’ collaborative skills reached 84.95%. A total of 51.35% of students fell into the high-to-very-high category, with the aspect of positive interdependence receiving the highest score (90.99%) and the aspect of group processing receiving the lowest score (73.65%). These findings indicate that the application of the Orff Method based on the Jigsaw Model has the potential to positively stimulate the collaborative skills of fifth-grade elementary school students, although reinforcement in the group processing aspect is still needed.